Analısıs Peran Pendıdıkan Karakter Dalam Aktıvıtas Belajar Peserta Dıdık di SDN Leuwınanggung Tasıkmalaya - Mega Tiara Irfani, Mega Tiara Irfani; Rakhmat, Cece; Indihadi , Dian (Jurnal Elementaria Edukasia, 2023)
This study aims to describe how the role of character education in student learning activities at SDN Leuwinanggung for third grade students and knowing the process of implementing the habituation activity program in the formation of religious, honest, disciplined and responsible character for students. This research is a qualitative research, the data analysis in this research is descriptive analysis technique. The research subjects were the Principal, Deputy Principal for Curriculum, Class III Guardian Teachers, Class III Students. Data collection techniques used in this research are Observation, Interview, Documentation. Data were analyzed through data reduction steps, data display and conclusion drawing. The results in this study based on the results of data collection indicate that the role of character education in student learning activities at SDN Leuwinanggung has a very good role in student learning activities in the classroom so that students can carry out the learning process actively, effectively, conducive and purposefully. learning can be achieved. The implementation of character education at SDN Leuwinanggung is carried out through habituation activities such as routine, spontaneous, programmed, exemplary activities.